Heterogeneity in brewing yeast populations - Pendlebury, Toby (2022)
During brewing fermentations, yeast cells are subjected to a range of stress factors including ethanol, osmotic and oxidative stress. These have an impact on population health, affecting fermentation consistency, efficiency, and quality of the product. Typically, the tolerance of a yeast culture to stress is assessed via analysis of the entire population generating mean data, assuming each cell has broadly equivalent characteristics. This can mask detail at the cellular level which can only be obtained by analysing individual cells. In this study, a range of yeast strains significant to the brewing industry were investigated for tolerance to a variety of environmental challenges. This was performed using a novel high throughput assay for investigating ‘population heterogeneity’, based on cell cytotoxicity. This revealed that some cells within a population were more tolerant to stresses than others. Furthermore, the dynamics of the stress response differed between strains in both the maximum tolerance and degree of heterogeneity. To identify potential sources of variation within populations, key cell organelles were analysed for variation in structural integrity. Yeast cells were also separated according to replicative age, by sorting based on bud scar material, this allowed for the physiological differences between daughter and aged cells to be investigated. Based on this analysis, we provide evidence to suggest that population variation is an innate inheritable characteristic. Subsequently, cell metabolites upregulated under stressed conditions were identified using metabolomics, this data was used this to conduct targeted single cell gene expression analysis, using a highly heterogenous and a less heterogeneous strain. From this, we were able to conclude that genes upregulated in response to stress were heterogenous in nature, matching the phenotypic data observed previously. We also demonstrate that the cause of phenotypic heterogeneity was likely a result of an accumulation of many heterogeneous gene expression events. Clusters were identified in specific groups of cells, implying the presence of population organisation, likely to be a ‘division of labour’ survival strategy. This data has implications for our understanding of strain specific fermentation limits and the techniques developed here may facilitate screening and prediction of the suitability of yeast strains for specific fermentation types.